ENCOUNTERING AND COUNTERING WORK STRESS: A MULTIVARIATE ANALYSIS OF THE OCCUPATIONAL STRESS AND COPING MECHANISMS OF FAST FOOD RESTAURANT PERSONNEL IN THE PHILIPPINES - Ereno, Joselito R.; Andrade, Kevin M.; Miyauchi, Shannen I.; Salinda, Roxy; Arevalo, Raizelle R.; Reyes, Janilyn (European Scientific Journal, ESJ, 2014)
Food is always viewed as an indispensable household necessity. Based on the 2009 Family Income and Expenditure Survey (FIES), 42.6% of the total expenditure of a typical Filipino household is solely being allocated for food (Limtingco, 2012). As the growing demand for food continues to escalate, fast food providers had proliferated both in the metro and rural provinces to help augment the need. In effect, the demand for human workforce for these companies had also escalated. However, at present, no available literature had yet explicated on the current psychological condition of the working personnel of these companies. Thus, this research is an exploratory attempt meant to delve on the various typologies and severity of stressors currently experienced by the food service personnel in the Philippines. Furthermore, this study statistically accounted for the coping mechanisms used by the fast food service personnel in treating their work related problems.